"Shrekorewolucja", czyli przełomowy charakter produkcji animowanych = "Shrek-revolution", or the groundbreaking nature of animated productions - Borowczyk, Paulina (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
In this article, I focus on presenting and discussing the aspects that contributed to the success of the first and second parts of the American production "Shrek". The discussed factors are predominantly characteristic of either animated or live-action movies. The formula proposed by the creators of "Shrek" proved effective to the extent that all the animations made after 2001 have been created in a similar way. Alluding to the world of popculture, absurd humor, parody, using famous actors` voices and applying the cutting-edge technologies are central to creating animated characters and their fairy-tale world.
Keywords: Shrek; filmy dubbingowane; dialogi filmowe; relacje intertekstualne; aluzje kulturowe; dubbed movies; movie dialogues; intertextual relationships; cultural references